Role of Epigallocatechin Gallate on In Vitro Model of Methylglyoxal-induced Amyloidogenesis - Kucukgul, Dr. Altug (Asian Journal of Pharmaceutics (AJP), 2016)
Introduction: The study aimed to investigate the potential effects of epigallocatechin gallate (EG) on the reflux of methylglyoxal (MG)-induced amyloidogenesis in human glioblastoma (U87) cells. Materials and Methods: The effective concentrations of MG and EG were investigated via Trypan blue test. Glyoxalase-1 (GLO-1), Î²-amyloid precursor protein (Î²APP), and Caspase 3 (Cas 3) expression levels were determined by quantitative real-time polymerase chain reaction and intracellular glutathione (GSH) contents of cells were measured. Results: MG at 250 Î¼M reduced viable cells by 33.4% as compared to control group. However, 5 Î¼M EG pre-treatment before MG prevented 22.4% of the cell loss caused by MG (P â‰¤ 0.05). MG stimulated Î²APP and Caspase 3 levels by 4.13- and 3.46-fold; however, EG pre-treatment inhibited these increases by 1.76 and 3.09, respectively. In addition, EG pre-treatment increased GLO-1 levels by 3.71-fold and GSH levels by 2.30-fold according to MG group. Conclusion: EG demonstrated protective effect against cell death on U87 cells by suppressing amyloidogenic factors and apoptotic stimuli induced by MG.